Cobertura periodística y corrientes de opinión sobre el indulto de Alberto Fujimori - Oblitas Bernal, Jorge David (2022)
The present work analyzes the journalistic coverage and the currents of opinion that were created about the frustrated pardon of Alberto Fujimori Fujimori in December 2017, the only former president sentenced for crimes against humanity who in Peruvian history requested and temporarily agreed to said grace. The investigation takes as reference the events broadcast on television that contributed to the public debate of the case, to identify the constitutive elements of public opinion. It also reconstructs the work routines that the journalists of the print media fulfilled, in the judicial coverage of the uneventful pardon, and collects their perspectives on what it meant to make this news known in accordance with the editorial lines of each journalistic company.